Fundamentals of Entrepreneurship ETR300 Paramedia/ Darrold Hansen Mathew... [et al.] - Mathew, Darrold Hansen; Mohd Zamri, Norfarahzila; Edwin, Danny; Zakaria, Nik Mohd Faris; Wahid, Mohd Akmal Naim (2009)
Paramedia is a new medium-sized event organizer company located in a trendy neighbourhood of Desa Ilmu, Kota Samarahan. The business is in the form of partnership, which consists of fifth members. Paramedia's emphasis will be on event organizing services. An emphasis on decoration and facilities is based on Paramedia's dedication to sustainable development. All partners are entitled to participate in the business management. We have agreed that Darrold Hansen Mathew as the General Manager, Danny ak Edwin as the Administration Manager, Norfarahzila as the Marketing Manager, Nik Mohd Faris bin Zakaria as the Operational Manager and Mohd Akmalnaim bin Wahid as the Financial Manager. The management will be lead by General Manager and assisted by other managers. The General Manager is responsible in controlling, leading, organizing, and planning the entire business. Administration is responsible for the entire jobs related to office 7 administration. The Marketing Executive is responsible in preparing marketing plan. This includes identifying the target market share, develop sales forecast and develop the marketing strategies. The operation of our business is controlled and monitored by Operation Executive. All workers who work in our company are working under operation manager. The Financial Executive will take the responsibility in financial matter such as preparing budget and financial statement for each department expenses.